2019
DOI: 10.1620/tjem.248.99
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan as a Promising Biomarker for Myocardial Damage

Abstract: Hyaluronan is a glycosaminoglycan, one of the chief components of the extracellular matrix. The aim of the present study is to investigate plasma hyaluronan levels among patients with acute myocardial infarction (AMI). This prospective study enrolled 56 consecutive patients with AMI who underwent percutaneous coronary intervention within 2 hours after admission. Plasma levels of hyaluronan were measured at the time of admission (baseline), and on the 7th and 30th day after AMI. Echocardiographic examinations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…This may indicate that alteration of regional endothelial shear stress and eroded plaques independently influenced the systemic change in HA levels in STEMI patients. Nevertheless, another study found that the plasma level of HA was significant higher in acute myocardial infarction group than normal, which was on contrary to our result (29). It is worth noting that we only examined the HA of which molecular size was larger than 35 kDa due to the limitation of ELISA kit.…”
Section: Discussioncontrasting
confidence: 99%
“…This may indicate that alteration of regional endothelial shear stress and eroded plaques independently influenced the systemic change in HA levels in STEMI patients. Nevertheless, another study found that the plasma level of HA was significant higher in acute myocardial infarction group than normal, which was on contrary to our result (29). It is worth noting that we only examined the HA of which molecular size was larger than 35 kDa due to the limitation of ELISA kit.…”
Section: Discussioncontrasting
confidence: 99%
“…Another component of ECM—hyaluronan—serves as a promising biomarker for myocardial damage among patients with acute myocardial infarction (AMI). In 56 patients plasma levels of hyaluronan were significantly elevated 30 day after AMI ( 53 ). Both fibronectin and hyaluronan were linked to cardiac allograft rejection as demonstrated in heart allografts in rats.…”
Section: Tlr Ligandsmentioning
confidence: 99%
“…The results in these different models indicate that HA has an essential role in cardiac repair following MI and IRI and, although it can act as a ligand for TLR2 and TLR4, questions its role as a detrimental DAMP. A recently published clinical study showed that the plasma HA levels are significantly increased in patients with acute MI and indicate that it has the potential to serve as a biomarker of myocardial damage but failed to establish a causal role between HA upregulation and cardiac damage (45).…”
Section: Hyaluronic Acidmentioning
confidence: 99%